Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Establishing best practice for N-nitrosamine read-across and surrogate selection - David J. Ponting; Gabriela de Oliveira Silveira; Philip Rowell; Crina I. Heghes; Adrian Fowkes; Christopher G. Barber (Regulatory Toxicology and Pharmacology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Personal exposures to air pollutants and respiratory health among brick kiln workers and household members - Laura Nicolaou; Evelyn Rowell; Chelsea Gaviola; Ram K. Chandyo; Arun K. Sharma; Laxman P. Shrestha; Santa Das; David L. Parker; Steven M. Thygerson; Joseph Jacob; Bojidar Rangelov; Ryoko Egashira; et al. (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Representation of precipitation and top-of-atmosphere radiation in a multi-model convection-permitting ensemble for the Lake Victoria Basin (East-Africa) - Nicole P. M. van Lipzig; Jonas Van de Walle; Danijel Belušić; Ségolène Berthou; Erika Coppola; Matthias Demuzere; Andreas H. Fink; Declan L. Finney; Russell Glazer; Patrick Ludwig; John H. Marsham; Grigory Nikulin; et al. (Climate Dynamics, 2023)
The CORDEX Flagship Pilot Study ELVIC (climate Extremes in the Lake VICtoria basin) was recently established to investigate how extreme weather events will evolve in this region of the world and to provide improved information for the climate impact community. Here we assess the added value of the convection-permitting scale simulations on the representation of moist convective systems over and around Lake Victoria. With this aim, 10 year present-day model simulations were carried out with five regional climate models at both PARameterized (PAR) scales (12–25 km) and Convection-Permitting (CP) scales (2.5–4.5 km), with COSMO-CLM, RegCM, AROME, WRF and UKMO. Most substantial systematic improvements were found in metrics related to deep convection. For example, the timing of the daily maximum in precipitation is systematically delayed in CP compared to PAR models, thereby improving the agreement with observations. The large overestimation in the total number of rainy events is alleviated in the CP models. Systematic improvements were found in the diurnal cycle in Top-Of-Atmosphere (TOA) radiation and in some metrics for precipitation intensity. No unanimous improvement nor deterioration was found in the representation of the spatial distribution of total rainfall and the seasonal cycle when going to the CP scale. Furthermore, some substantial biases in TOA upward radiative fluxes remain. Generally our analysis indicates that the representation of the convective systems is strongly improved in CP compared to PAR models, giving confidence that the models are valuable tools for studying how extreme precipitation events may evolve in the future in the Lake Victoria basin and its surroundings.

Impact of climate change on volcanic processes: current understanding and future challenges - Thomas J. Aubry; Jamie I. Farquharson; Colin R. Rowell; Sebastian F. L. Watt; Virginie Pinel; Frances Beckett; John Fasullo; Peter O. Hopcroft; David M. Pyle; Anja Schmidt; John Staunton Sykes (Bulletin of Volcanology, 2022)
The impacts of volcanic eruptions on climate are increasingly well understood, but the mirror question of how climate changes affect volcanic systems and processes, which we term “climate-volcano impacts”, remains understudied. Accelerating research on this topic is critical in view of rapid climate change driven by anthropogenic activities. Over the last two decades, we have improved our understanding of how mass distribution on the Earth’s surface, in particular changes in ice and water distribution linked to glacial cycles, affects mantle melting, crustal magmatic processing and eruption rates. New hypotheses on the impacts of climate change on eruption processes have also emerged, including how eruption style and volcanic plume rise are affected by changing surface and atmospheric conditions, and how volcanic sulfate aerosol lifecycle, radiative forcing and climate impacts are modulated by background climate conditions. Future improvements in past climate reconstructions and current climate observations, volcanic eruption records and volcano monitoring, and numerical models all have a role in advancing our understanding of climate-volcano impacts. Important mechanisms remain to be explored, such as how changes in atmospheric circulation and precipitation will affect the volcanic ash life cycle. Fostering a holistic and interdisciplinary approach to climate-volcano impacts is critical to gain a full picture of how ongoing climate changes may affect the environmental and societal impacts of volcanic activity.

How a typical West African day in the future-climate compares with current-climate conditions in a convection-permitting and parameterised convection climate model - Rory G. J. Fitzpatrick; Douglas J. Parker; John H. Marsham; David P. Rowell; Lawrence S. Jackson; Declan Finney; Chetan Deva; Simon Tucker; Rachael Stratton (Climatic Change, 2020)
Current-climate precipitation and temperature extremes have been identified by decision makers in West Africa as among the more impactful weather events causing lasting socioeconomic damage. In this article, we use a plausible future-climate scenario (RCP8.5) for the end of the twenty-first century to explore the relative commonness of such extremes under global warming. The analysis presented considers what a typical day in the future climate will feel like relative to current extrema. Across much of West Africa, we see that the typical future-climate day has maximum and minimum temperatures greater than 99.5% of currently experienced values. This finding exists for most months but is particularly pronounced during the Boreal spring and summer. The typical future precipitation event has a daily rainfall rate greater than 95% of current storms. These findings exist in both a future scenario model run with and without parameterised convection, and for many of the Coupled Model Inter-comparison Project version 5 ensemble members. Additionally, agronomic monsoon onset is projected to occur later and have greater inter-annual variability in the future. Our findings suggest far more extreme conditions in future climate over West Africa. The projected changes in temperature and precipitation could have serious socioeconomic implications, stressing the need for effective mitigation given the potential lack of adaptation pathways available to decision makers.

Towards Spatially Explicit Quantification of Pre- and Postfire Fuels and Fuel Consumption from Traditional and Point Cloud Measurements - Andrew T Hudak; Akira Kato; Benjamin C Bright; E Louise Loudermilk; Christie Hawley; Joseph C Restaino; Roger D Ottmar; Gabriel A Prata; Carlos Cabo; Susan J Prichard; Eric M Rowell; David R Weise (Forest Science, 2020)
Methods to accurately estimate spatially explicit fuel consumption are needed because consumption relates directly to fire behavior, effects, and smoke emissions. Our objective was to quantify sparkleberry (Vaccinium arboretum Marshall) shrub fuels before and after six experimental prescribed fires at Fort Jackson in South Carolina. We used a novel approach to characterize shrubs non-destructively from three-dimensional (3D) point cloud data collected with a terrestrial laser scanner. The point cloud data were reduced to 0.001 m–3 voxels that were either occupied to indicate fuel presence or empty to indicate fuel absence. The density of occupied voxels was related significantly by a logarithmic function to 3D fuel bulk density samples that were destructively harvested (adjusted R2 = .32, P < .0001). Based on our findings, a survey-grade Global Navigation Satellite System may be necessary to accurately associate 3D point cloud data to 3D fuel bulk density measurements destructively collected in small (submeter) shrub plots. A recommendation for future research is to accurately geolocate and quantify the occupied volume of entire shrubs as 3D objects that can be used to train models to map shrub fuel bulk density from point cloud data binned to occupied 3D voxels.

Future changes and uncertainty in decision-relevant measures of East African climate - F. Jorge Bornemann; David P. Rowell; Barbara Evans; Dan J. Lapworth; Kamazima Lwiza; David M.J. Macdonald; John H. Marsham; Kindie Tesfaye; Matthew J. Ascott; Celia Way (Climatic Change, 2019)

Improved climatological precipitation characteristics over West Africa at convection-permitting scales - Ségolène Berthou; David P. Rowell; Elizabeth J. Kendon; Malcolm J. Roberts; Rachel A. Stratton; Julia A. Crook; Catherine Wilcox (Climate Dynamics, 2019)

Plant host relationships of three lineages of the gall-inducing fly Fergusonina Malloch (Diptera: Fergusoninidae) on Eucalyptus L’Hérit. - Michaela F. Purcell; Andrew H. Thornhill; Thomas C. Wallenius; David K. Yeates; David M. Rowell (Arthropod-Plant Interactions, 2018)

Seasonal temperature is associated with Parkinson’s disease prescriptions: an ecological study - David Rowell; Son Nghiem; Sreeram Ramagopalan; Ute-Christiane Meier (International Journal of Biometeorology, 2017)

Teleconnections between Ethiopian rainfall variability and global SSTs: observations and methods for model evaluation - Mekonnen Adnew Degefu; David P. Rowell; Woldeamlak Bewket (Meteorology and Atmospheric Physics, 2017)

Can climate projection uncertainty be constrained over Africa using metrics of contemporary performance? - David P. Rowell; Catherine A. Senior; Michael Vellinga; Richard J. Graham (Climatic Change, 2016)

Annually laminated sediments from Onondaga Lake, New York (USA) provide a basis for high-resolution studies of lake degradation and recovery - H. Chandler Rowell; Richard F. Bopp; Feng Peng; David J. Velinsky; Jay A. Bloomfield (Journal of Paleolimnology, 2015)

Genome size and chromosome number in velvet worms (Onychophora) - Nicholas W. Jeffery; Ivo S. Oliveira; T. Ryan Gregory; David M. Rowell; Georg Mayer (Genetica, 2012)

Sources of uncertainty in future changes in local precipitation - David P. Rowell (Climate Dynamics, 2012)

Nitrogen isotopes in otoliths reconstruct ancient trophic position - Kirsten Rowell; David L. Dettman; Robert Dietz (Environmental Biology of Fishes, 2010)

Mechanisms and reliability of future projected changes in daily precipitation - Elizabeth Jane Kendon; David P. Rowell; Richard G. Jones (Climate Dynamics, 2010)

Intercomparison and analyses of the climatology of the West African Monsoon in the West African Monsoon Modeling and Evaluation project (WAMME) first model intercomparison experiment - Yongkang Xue; Fernando De Sales; W. K.-M. Lau; Aaron Boone; Jinming Feng; Paul Dirmeyer; Zhichang Guo; Kyu-Myong Kim; Akio Kitoh; Vadlamani Kumar; Isabelle Poccard-Leclercq; Natalie Mahowald; et al. (Climate Dynamics, 2010)

The WAMME regional model intercomparison study - Leonard M. Druyan; Jinming Feng; Kerry H. Cook; Yongkang Xue; Matthew Fulakeza; Samson M. Hagos; Abdourahamane Konaré; Wilfran Moufouma-Okia; David P. Rowell; Edward K. Vizy; Seidou Sanda Ibrah (Climate Dynamics, 2010)

Understanding uncertainty in future projections for the tropical Atlantic: relationships with the unforced climate - Peter Good; Jason A. Lowe; David P. Rowell (Climate Dynamics, 2009)

Changes in European ecosystem productivity and carbon balance driven by regional climate model output - PABLO MORALES; THOMAS HICKLER; DAVID P. ROWELL; BENJAMIN SMITH; MARTIN T. SYKES (Global Change Biology, 2007)
Climate change resulting from the enhanced greenhouse effect together with the direct effect of increased atmospheric CO 2 concentrations on vegetation growth are expected to produce changes in the cycling of carbon in terrestrial ecosystems. Impacts will vary across Europe, and regional‐scale studies are needed to resolve this variability. In this study, we used the LPJ‐GUESS ecosystem model driven by a suite of regional climate model (RCM) scenarios from the European Union (EU) project PRUDENCE to estimate climate impacts on carbon cycling across Europe. We identified similarities and discrepancies in simulated climate impacts across scenarios, particularly analyzing the uncertainties arising from the range of climate models and emissions scenarios considered. Our results suggest that net primary production (NPP) and heterotrophic respiration (Rh) will generally increase throughout Europe, but with considerable variation between European subregions. The smallest NPP increases, and in some cases decreases, occurred in the Mediterranean, where many ecosystems switched from sinks to sources of carbon by 2100, mainly as a result of deteriorating water balance. Over the period 1991–2100, modeled climate change impacts on the European carbon balance ranged from a sink of 11.6 Gt C to a source of 3.3 Gt C, the average annual sink corresponding with 1.85% of the current EU anthropogenic emissions. Projected changes in carbon balance were more dependent on the choice of the general circulation model (GCM) providing boundary conditions to the RCM than the choice of RCM or the level of anthropogenic greenhouse gases emissions.

A tale of two flatties: different responses of two terrestrial flatworms to past environmental climatic fluctuations at Tallaganda in montane southeastern Australia - PAUL SUNNUCKS; MARK J. BLACKET; JODY M. TAYLOR; CHESTER J. SANDS; SHERRYN A. CIAVAGLIA; RYAN C. GARRICK; NOEL N. TAIT; DAVID M. ROWELL; ALEXANDRA PAVLOVA (Molecular Ecology, 2006)
Comparative phylogeographic studies of animals with low mobility and/or high habitat specificity remain rare, yet such organisms may hold fine‐grained palaeoecological signal. Comparisons of multiple, codistributed species can elucidate major historical events. As part of a multitaxon programme, mitochondrial cytochrome oxidase I (COI) variation was analysed in two species of terrestrial flatworm, Artioposthia lucasi and Caenoplana coerulea . We applied coalescent demographic estimators and nested clade analysis to examine responses to past, landscape‐scale, cooling‐drying events in a model system of montane forest (Tallaganda). Correspondence of haplotype groups in both species to previously proposed microbiogeographic regions indicates at least four refuges from cool, dry conditions. The region predicted to hold the highest quality refuges (the Eastern Slopes Region), is indicated to have been a long‐term refuge in both species, but so are several other regions. Coalescent analyses suggest that populations of A. lucasi are declining, while C. coerulea is expanding, although stronger population substructure in the former could yield similar patterns in the data. The differences in spatial and temporal genetic variation in the two species could be explained by differences in ecological attributes: A. lucasi is predicted to have lower dispersal ability but may be better able to withstand cold conditions. Thus, different contemporary population dynamics may reflect different responses to recent (Holocene) climate warming. The two species show highly congruent patterns of catchment‐based local genetic endemism with one another and with previously studied slime‐mould grazing Collembola.

A Demonstration of the Uncertainty in Projections of UK Climate Change Resulting from Regional Model Formulation - David P. Rowell (Climatic Change, 2006)

Causes and uncertainty of future summer drying over Europe - David P. Rowell; Richard G. Jones (Climate Dynamics, 2006)

A scenario of European climate change for the late twenty-first century: seasonal means and interannual variability - David P. Rowell (Climate Dynamics, 2005)

Effects of Experimental Otter Trawling on Surficial Sediment Properties of a Sandy‐Bottom Ecosystem on the Grand Banks of Newfoundland - Peter Schwinghamer; Donald C. Gordon; Terence W. Rowell; Jens Prena; David L. McKeown; G. Sonnichsen; J. Y. Guigné (Conservation Biology, 1998)
We conducted a 3‐year experiment on the effects of otter trawling on benthic habitat and communities on a sandy‐bottom ecosystem of the Grand Banks of Newfoundland that has supported commercial fisheries. Each year, three 13‐km‐long corridors were trawled 12 times with an Engel 145 otter trawl, creating a disturbance zone 120–250 m wide. Using a variety of oceanographic instruments, measurements were made before and after trawling to document effects. Trawling had no detectable effect on sediment grain size. Tracks made by trawl doors were readily visible on the sea floor immediately after trawling and 10 weeks later; in some cases they were still faintly visible after 1 year. Acoustic data indicated that trawling increased the topographic relief or roughness of surficial sediments and changed small‐scale biogenic sediment structures down to depths of 4.5 cm. Video observations in trawled corridors revealed that organisms and shells tended to be organized into linear features parallel to the corridor axis. They also demonstrated that trawling reduces both surficial biogenic sediment structure and the abundance of flocculated organic matter; untrawled sediments had a hummocky, mottled appearance, whereas trawled sediments were smoother and cleaner. These changes combined to give the trawled corridors a lighter appearance in color. It appears that the physical effects of otter trawling observed in this experiment are moderate and that recovery occurs in about a year. The biological effects of this experimental trawling have yet to be examined. Efectos del Arrastre Experimental en las Propiedades de Sedimentos Superficiales de un Ecosistema de Fondo Arenoso de los Grande Bancos de Terranova Un experimento de tres años sobre los efectos del arrastre en hábitat bentónico y sus comunidades fue realizado en un ecosistema arenoso que soporta pesquerías comerciales de los Grandes Bancos de Terranova. Cada año, tres corredores de 13 km de largo fueron arrastrados 12 veces con una red de arrastre Engel, creando una zona de perturbación de 120‐250 m de ancho. Para documentar los efectos se realizaron mediciones antes y después del arrastre usando una variedad de instrumentos oceanográficos. Los arrastres no tuvieron efectos detectables en el tamaño de grano del sedimento. Las marcas hechas por las puertas del arrastre fueron fácilmente visibles en el fondo inmediatamente después del arrastre y hasta 10 semanas después; en algunos casos las marcas fueron visibles después de un año. Los datos acústicos indican que el arrastre incrementa el relieve topográfico o la aspereza del sedimento superficial y cambia las estructuras biogénicas de pequeña escala del sedimento hasta una profundidad de 4.5 cm. Observaciones de video en corredores de arrastre revelan que los organismos y conchas tienden a estar organizados en forma lineal y paralelos a los ejes del corredor. Los videos también demostraron que el arrastre reduce tanto la estructura biogénica superficial del sedimento como la abundancia de materia orgánica floculada; sedimentos que no han sido expuestos a arrastres tuvieron una aparencia irregular y moteada, mientras que los expuestos a arrastres fueron suaves y limpios. Estos cambios se combinan para dar a los corredores arrastrados una apariencia clara en color. Aparentemente los efectos físicos del arrastre observados en este experimento son moderados y su recuperación ocurre en aproximadamente un año. Los efectos biológicos de este experimento de arrastre aún tienen que ser examinados.

North Atlantic and European seasonal predictability using an ensemble of multidecadal atmospheric GCM simulations - John R. Davies; David P. Rowell; Chris K. Folland (International Journal of Climatology, 1997)